Insect Life - Time-Life Books (Time-Life Books : Hong Kong, 1994)
This volume presents an engaging overview of insect biology and diversity, using a visually rich Q&A-style format. It explains: Anatomy and life cycles of insects Behaviors like feeding, defense mechanisms, and colony organization Ecological roles of different insect species Illustrated with full-color photos, diagrams, and simple explanations, targeting young and general readers.
Keywords: Insects